(untitled) (AMJ (Advanced Medical Journal), 2023)
Background and objectives: To evaluate the role of dorzolamide –timolol fixed combination in lowering intraocular pressure (IOP) after cataract surgery. Methods: The study included 94 eyes of 89 patients who underwent cataract surgery and intraocular lens implantation. Patients planed for phacoemulsification were assigned to 1 of 2 groups. The treatment group received 1 drop of dorzolamide-timolol fixed combination immediately after surgery, and the control group received no treatment. The IOP was measured preoperatively and at 6 hours and 24 hours post- operatively. Results: The mean IOP change was lower in the treatment group than in the control group at 6 hours postoperatively. The difference between the mean IOP a value of the two groups at 6 hours postoperatively was found to be statistically significant. Twenty-four hours after the surgery, the mean IOP change was still higher in the control group when compared to the treatment group. Conclusions: The fixed combination dorzolamide-timolol can effectively lower IOP after phacoemulsification cataract surgery.